Diseño de un sistema de gestión de calidad bajo la estructura de la ISO 9001 versión 2015 para la empresa Abelpán ubicada en la ciudad de Santa Marta - Triana Patiño, Erick Jhomar; Rubio Lopez, Gustavo Andres (Universidad Antonio Nariño, 2021)
This investigative work determines the activities necessary to carry out the quality management and standardization of the processes in the bakery company Abelpán in the city of Santa Marta, based on the ISO 9001: 2015 Standard and the guidelines established to carry out the SGC. The project arose as a response to the poor organization and documentation of the bakery processes, in addition to the low contextualization of the quality management concept and the customerdirected approach; Therefore, based on the above, the opportunity was born to start this work with the idea of designing a quality management system for the bakery that would allow solving the aforementioned problems. In the first instance, a diagnosis of the current situation of the company was carried out, seeking to understand its organizational context and the level of compliance with respect to the requirements of the aforementioned standard. Then, the creation and reorganization of the processes taken into account in the SGC was carried out, starting from a process map, highlighting the creation of the quality management process for the bakery; Each process had a characterization, procedures and control formats for its standardization. Next, management indicators and the formats to calculate them were developed, allowing the performance of each of the processes worked to be evaluated. Finally, the quality manual of the system is drawn up and delivered to the bakery together with the designed quality management system, in a digitized way